Exploring the Effect of the COVID-19 Pandemic on the Dental Team: Preparedness, Psychological Impacts and Emotional Reactions - Humphris, Gerry; Knights, Jennifer; Beaton, Laura; Araujo, Marianna; Yuan, Siyang; Clarkson, Jan; Young, Linda; Freeman, Ruth (Frontiers in Oral Health, 2021)
Background: The COVID-19 pandemic has placed increased demands on clinical staff in primary dental care due to a variety of uncertainties. Current reports on staff responses have tended to be brief enquiries without some theoretical explanation supported by developed measurement systems. Aim: To investigate features of health and well-being as an outcome of the uncertainties surrounding COVID-19 for dentists and dental health professionals in primary dental care and for those in training. In addition, the study examined the well-being indices with reference to normative values. Finally a theoretical model was explored to explain depressive symptoms and investigate its generalisability across dentists and dental health professionals in primary dental care and those in postgraduate training. Methods: A cross-sectional survey of dental trainees and primary dental care staff in Scotland was conducted in June to October 2020. Assessment was through “Portal,” an online tool used for course bookings/management administered by NHS Education for Scotland. A non-probability convenience sample was employed to recruit participants. The questionnaire consisted of four multi-item scales including: preparedness (14 items of the DPPPS), burnout (the 9 item emotional exhaustion subscale and 5 items of the depersonalisation subscale of the MBI), the 22 item Impact of Event Scale-Revised, and depressive symptomatology using the Patient Health Questionnaire-2. Analysis was performed to compare the levels of these assessments between trainees and primary dental care staff and a theoretically based path model to explain depressive symptomology, utilising structural equation modelling. Results: Approximately, 27% of all 329 respondents reported significant depressive symptomology and 55% of primary care staff rated themselves as emotionally exhausted. Primary care staff (n = 218) felt less prepared for managing their health, coping with uncertainty and financial insecurity compared with their trainee (n = 111) counterparts (all p's < 0.05). Depressive symptomology was rated higher than reported community samples (p < 0.05) The overall fit of the raw data applied to the theoretical model confirmed that preparedness (negative association) and trauma associated with COVID-19 (positive association) were significant factors predicting lowered mood (chi-square = 46.7, df = 21, p = 0.001; CFI = 0.98, RMSEA = 0.06, SRMR = 0.03). Burnout was indirectly implicated and a major path from trauma to burnout was found to be significant in primary care staff but absent in trainees (p < 0.002). Conclusion: These initial findings demonstrate the possible benefit of resourcing staff support and interventions to assist dental staff to prepare during periods of high uncertainty resulting from the recent COVID-19 pandemic.